2020
DOI: 10.1111/1750-3841.15107
|View full text |Cite
|
Sign up to set email alerts
|

Novel processing techniques and spinach juice: Quality and safety improvements

Abstract: In this study, the combined effect of ultrasound (US) and pulsed electric field (PEF) techniques was analyzed for the quality improvement and microbial safety of spinach juice. The spinach juice was treated with US at frequency of 40 kHz, radiating power of 200 W below 30 ± 2°C temperature for 21 min in ultrasonic bath cleaner, and PEF treatment (pulse frequency: 1 kHz, flow rate: 60 mL/min, temperature: 30 ± 2°C, time: 335 µs, electric field strength 9 kV/cm) was done. In results, the combined (US-PEF) treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 50 publications
(60 reference statements)
2
37
1
Order By: Relevance
“…We aim to investigate the combined impact of PEF and US treatment on the quality of spinach juice to define the best processing conditions to ensure the best quality of spinach juice. The combined impact of US and PEF processing on microbiological analysis in spinach juice was already published in our article (Manzoor, Ahmed, et al., 2020).…”
Section: Introductionmentioning
confidence: 62%
“…We aim to investigate the combined impact of PEF and US treatment on the quality of spinach juice to define the best processing conditions to ensure the best quality of spinach juice. The combined impact of US and PEF processing on microbiological analysis in spinach juice was already published in our article (Manzoor, Ahmed, et al., 2020).…”
Section: Introductionmentioning
confidence: 62%
“…The infrared spectra analysis also identified the vibration signs of biofuel from the waste date palm. The results revealed that wave numbers 2,900 and 3,300 cm −1 link to CH and OH molecule groups, respectively (Boulal et al., 2016; Manzoor et al., 2019, 2020; Mehani et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound is an inexpensive technique that reduced energy consumption, as well as processing time (Manzoor et al., 2019; Rahaman et al., 2019; Siddeeg et al., 2019a). The influence of ultrasound on the freshness of liquid juices has been studied in spinach juice (Manzoor et al., 2020), blackberry juice (Cervantes‐Elizarrarás et al., 2017), pear juice (Saeeduddin et al., 2016), and strawberry juice (Bhat & Goh, 2017). The outcome of these investigations is to maintain the quality of juices without losing its bioactive compounds and inactivate pathogenic microbes.…”
Section: Introductionmentioning
confidence: 99%